Reducing the Environmental Impact of Denim: A Comparative Study of Green and Conventional Manufacturing Practices - Kazi Rezwan Hossain; Mohammad Faizur Rahman (Textile & Leather Review)
Denim manufacturing, from cotton farming to garment production, carries significant environmental impacts. Despite introducing sustainability within the denim industry, the environmental benefits of related practices are not thoroughly assessed and contrasted with conventional manufacturing practices. This study aims to evaluate and compare the environmental impacts of sustainable and traditional denim manufacturing processes in Bangladesh through a Life Cycle Assessment. Adhering to ISO 14040/14044:2006 standards and utilising the ReCiPe 2016 Midpoint (H) assessment, this study investigated key environmental indicators, including terrestrial acidification, eutrophication, land occupation, water consumption, abiotic depletion, and greenhouse gas emissions. Notable findings reveal that yarn and fabric production contribute to 56% of greenhouse gas emissions and 45% of terrestrial acidification, while cotton cultivation accounts for 92% of water consumption and 69% of land use. Compared to traditional methods, green manufacturing practices achieve reductions in greenhouse gas emissions and water use by over 60% and 21%, respectively. These findings underscore the potential for sustainable practices to mitigate the environmental footprint of denim production while highlighting areas for further improvement. This study delivers critical insights for advancing sustainability in the denim industry.